Research on the Spatial Distribution Characteristics of the Customs House in Kwangtung in Modern Times Based on GIS - Mujun Li, Qiuming Wang, Zhaoming Du, Ruirui Huang, Jun Chen, Qionglin Liu (Forest Chemicals Review, 1970)
The Custom House is the core building for the main function of the “Foreign Customs” and the core geographical location of the customs districts in modern China. They are also the most prominent structure in China’s modern treaty port city. The nuclear density, direction distribution, and layout relationships of several Customs Houses in Kwangtung are used to quantitatively analyze their location and spatial distribution characteristics.This research is trying to provideareference for the historical architecture context in our trade port cities during thecontemporary urban construction in China.